Dante's Tenzone with Forese Donati : the reprehension of vice - Alfie, Fabian (Toronto Italian studies., 2011)
"'And by now, mind, it's too late to redeem your debts by giving up guzzling.' Dante's poetic correspondence (or tenzone) with Forese Donati, a relative of his wife, was rife with crude insults: the two men derided one another on topics ranging from sexual dysfunction and cowardice to poverty and thievery. But in his Commedia, rather than denying this correspondence, Dante repeatedly acknowledged and evoked the memory of his youthful put-downs.